Specialisation and employment development in Germany: Analysis at regional level - Julia Kowalewski (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2010)
While the number of employees subject to social insurance contributions in Germany remained nearly constant from 1998 to 2007, there have been strong differences in regional and sectoral growth rates. The aim of this paper is to analyse the impact of the sector structure of a region on employment growth in Germany during this period. It will provide new findings about the impact of sector specific localisation effects on employment growth. If specialisation affects regional employment growth it is expected to be important for regional and labour market policies. Moreover, the paper deals with the question weather the sectoral structure of the regions fosters convergence or divergence, i.e. increasing specialisation of the regions. The empirical results show that the economic structures in Germany slowly converge.
Keywords: 330; regional specialisation; German regions; shift-share regression